2020
DOI: 10.1016/j.fcr.2020.107819
|View full text |Cite
|
Sign up to set email alerts
|

Border-row proportion determines strength of interspecific interactions and crop yields in maize/peanut strip intercropping

Abstract: Strip intercropping enables increases in yields and ecological services in agriculture. Crop yields of species grown in strip intercropping are often related to the yield responses (increases or decreases) in the outer rows of the strips: the border rows. This suggests that the yield response can be modulated by changing the proportion of border rows in the field. Here we studied the relationship between component species yields and proportion of border rows in strip intercrops of maize (Zea mays L.) and peanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…Peanut, on the other hand, improves available nitrogen in the soil of maize, as peanut is able to fix the atmospheric N 2 with rhizobia (Inal & Gunes, 2008). Previous studies on maize and peanut intercropping did not show a significant improvement on yield in semi‐arid environment (Wang et al., 2020; Zhang et al., 2020). We hypothesized that increasing the plant density of maize, a major contributor to yield advantage in the intercropping, might enhance the land productivity.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Peanut, on the other hand, improves available nitrogen in the soil of maize, as peanut is able to fix the atmospheric N 2 with rhizobia (Inal & Gunes, 2008). Previous studies on maize and peanut intercropping did not show a significant improvement on yield in semi‐arid environment (Wang et al., 2020; Zhang et al., 2020). We hypothesized that increasing the plant density of maize, a major contributor to yield advantage in the intercropping, might enhance the land productivity.…”
Section: Introductionmentioning
confidence: 81%
“…The main disadvantage for farming is the shortage of adapted machinery and related additional labor costs. The widen the crop strips, such as four rows maize with four rows peanut or six rows maize with six rows peanut, might also be reasonable configurations when take machinery into account (Wang et al., 2020). It is necessary and important to use optimal plant densities in the pure stand when calculating the LER of intercropping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the benefits of mutual interactions between adjacent allospecific plants, e. g., facilitation in water and nutrient uptake, which are maximized 3 , 4 . Several studies tested wider-strip widths and revealed that intercropping systems with wider-strips of 3 m 5 , 3.1 m 6 , 3.3 m 7 , 3.4 m 8 , and 6 m 9 achieved the highest LER compared to narrow-strips. Therefore, intercropping of crops with larger operating strips would be easier to manage with existing farm machinery, and it will produce high profits for farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Neighboring species show a strong interaction when individuals are more densely packed (Kennedy et al, 2002;Rayburn and Schupp., 2013). In mixed cropping systems, intercropping primarily utilizes the advantages of species interactions by adjusting the planting distances between species (Ma et al, 2007;Wang et al, 2020). Because species interactions can be controlled by the sizes of conspecific patches at seeding, it is possible to test the association of neighbor-effect intensity with the scale of facilitation or competition in plant communities and further quantify the intensity of negative and positive plant interactions.…”
Section: Introductionmentioning
confidence: 99%